MicroRNA-155 mediates multiple gene regulations pertinent to the role of human adipose-derived mesenchymal stem cells in skin regeneration - Shahin, Hady; Belcastro, Luigi; Das, Jyotirmoy; Perdiki Grigoriadi, Marina; Saager, Rolf B.; Steinvall, Ingrid; Sjöberg, Folke; Olofsson, Pia; Elmasry, Moustafa; El-Serafi, Ahmed T. (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction: The role of Adipose-derived mesenchymal stem cells (AD-MSCs) in skin wound healing remains to be fully characterized. This study aims to evaluate the regenerative potential of autologous AD-MSCs in a non-healing porcine wound model, in addition to elucidate key miRNA-mediated epigenetic regulations that underlie the regenerative potential of AD-MSCs in wounds. Methods: The regenerative potential of autologous AD-MSCs was evaluated in porcine model using histopathology and spatial frequency domain imaging. Then, the correlations between miRNAs and proteins of AD-MSCs were evaluated using an integration analysis in primary human AD-MSCs in comparison to primary human keratinocytes. Transfection study of AD-MSCs was conducted to validate the bioinformatics data. Results: Autologous porcine AD-MSCs improved wound epithelialization and skin properties in comparison to control wounds. We identified 26 proteins upregulated in human AD-MSCs, including growth and angiogenic factors, chemokines and inflammatory cytokines. Pathway enrichment analysis highlighted cell signalling-associated pathways and immunomodulatory pathways. miRNA-target modelling revealed regulations related to genes encoding for 16 upregulated proteins. miR-155-5p was predicted to regulate Fibroblast growth factor 2 and 7, C-C motif chemokine ligand 2 and Vascular cell adhesion molecule 1. Transfecting human AD-MSCs cell line with anti-miR-155 showed transient gene silencing of the four proteins at 24 h post-transfection. Discussion: This study proposes a positive miR-155-mediated gene regulation of key factors involved in wound healing. The study represents a promising approach for miRNA-based and cell-free regenerative treatment for difficult-to-heal wounds. The therapeutic potential of miR-155 and its identified targets should be further explored in-vivo.